Predictive factors for neonatal survival in women with periviable preterm rupture of the membranes. (November 2013) - Acaia, Barbara; Crovetto, Francesca; Ossola, Manuela W.; Nozza, Silvia; Baffero, Giulia Maria; Somigliana, Edgardo; Pietrasanta, Carlo; Pugni, Lorenza; Mosca, Fabio; Fedele, Luigi
Abstract Objective: To identify clinical, hematological or instrumental factors available at the time of the diagnosis that may predict neonatal survival in periviable preterm premature rupture of the membranes (PROM). Methods: We report on a cohort (n = 85) of women with periviable PROM (14–23.6 weeks' gestation) occurring over a 10-year period in a single institution. The main outcome chosen was the survival rate beyond the neonatal period. Variables considered were those available at 24 h after admission. Results: The overall survival rate was 49%. In the multivariate analysis, significant contributions for the prediction of neonatal survival were provided by four variables: genetic amniocentesis-related cause of PROM (p < 0.001), gestational age at PROM (p = 0.019), CRP > 1 mg/dl within 24 h after admission (p = 0.042) and oligohydramnios (largest vertical pocket ≤2 cm) (p = 0.041). The corresponding adjusted odds ratio (OR)s were 73.9 (95% CI: 7.9–694.7), 1.5 (95% CI: 1.1–2.0) per week, 0.26 (95% CI: 0.07–0.95) and 0.20 (95% CI: 0.04–0.93), respectively. Conclusions: Genetic amniocentesis-related cause of PROM, gestational age at PROM, C-reactive protein >1 mg/dl and oligohydramnios are significantly associated with survival in women with periviable PROM. The evaluation of these few and easily available variables may help physicians and patients in the decision-making process of this demanding condition.